Iridoid Esters from Tabebuia avellanedae and Their In Vitro Anti-inflammatory Activities - Zhang, Li; Hasegawa, Isao; Ohta, Tomihisa (Planta Medica, 2017)
A phytochemical investigation of the inner bark of Tabebuia avellanedae Lorentz ex Griseb was carried out by various chromatographic techniques, resulting in the isolation and characterization of eight new iridoid esters, namely Avelladoids A–H (1-8). Their chemical structures were elucidated on the basis of extensive spectroscopic analyses, especially 2D NMR experiments and HRMS data. The anti-inflammatory effects of 1–8 were determined on an LPS-stimulated RAW 264.7 cell line. Among them, compounds 1, 2, and 3 exhibited anti-inflammatory activities by inhibition of NO and PGE2 production in a dose-dependent manner, without altering cell viability.
Keywords: Bignoniaceae; Tabebuia avellanedae; iridoid esters; RAW 264.7 cells; anti-inflammatory; NO; PGE2